(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The M4 Wave Energy Demonstrator was deployed in King George Sound, Albany, over southern summer 2024-25. The project was funded by the Blue Economy CRC and State Government of Western Australia, to enhance confidence and knowledge in wave energy. This paper addresses the impact of the project, in terms of the progress made by the M4 concept, the community context of the project, and impact on the international wave energy landscape. Insights drawn from planning, deployment and decommissioning phases of the project will also be discussed. This includes the challenges of international procurement, systems integration and marine operations.